Experiences, challenges, gaps, and strategies for counselling persons presenting with advanced HIV-associated meningitis in Uganda - Alisat Sadiq; Richard Kwizera; Tadeo K Kiiza; Peruth Ayebare; Cynthia Ahimbisibwe; Jane Frances Ndyetukira; David R Boulware; David B. Meya (AIDS Research and Therapy)
Abstract Background Advanced HIV disease (AHD) is still a significant problem in Uganda despite the test-and-treat strategy and the increased access to antiretroviral therapy (ART). Meningitis remains a major cause of morbidity and mortality in people with AHD. HIV counselling is essential and plays an important role in managing persons with AHD-related meningitis. We sought to describe the experiences and challenges we faced during counselling of these individuals, highlighting the strategies, gaps and how we can fill them. Methods First, we describe our experience and major challenges in counselling people with AHD-related meningitis. Second, we describe the strategies we used to overcome each of these challenges. Third, we highlight the health system gaps and recommend solutions. Results Major challenges include the presence of altered mental status, unknown HIV status at admission, non-disclosure of HIV status to family, insufficient ART history, caretakers-related challenges, pill burden, multiple drug side effects, invasive clinical procedures, myths about medical procedures, poverty, lack of privacy during counselling in the wards, patients/caretakers seeking alternative non-medical interventions including religious, traditional, and herbal therapies before and after initiating meningitis treatment. Conclusions Persons with AHD-related meningitis need daily and special consideration during counselling as part of the package of care to improve treatment outcomes. Trial registrations NCT01075152 (23 Feb 2010), NCT01802385 (28 Feb 2013), ISRCTN42218549 (24 April 2018), ISRCTN72509687 (13 July 2017), NCT04031833 (01 January 2019), ISRCTN15668391 (23 May 2019), ISRCTN18437550 (05/11/2021).